2016
DOI: 10.1002/asna.201612346
|View full text |Cite
|
Sign up to set email alerts
|

High‐energy monitoring of Seyfert galaxies: The case of NGC 4593

Abstract: We discuss preliminary results from a joint XMM-Newton and NuSTAR monitoring program on the active galactic nucleus NGC 4593, consisting of 5 × 20 ks observations, spaced by two days, performed in January 2015. The source is found to be variable, both in flux and spectral shape, on time scales as short as a few ks. The spectrum clearly softens when the source brightens. A simple timing analysis suggests the presence of a variable soft excess that correlates with the primary continuum.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Above 0.5 counts/s there is a very slight softening of the spectrum with increasing count rate. This spectral softening is similar to that found in NGC 4593 by Ursini et al (2016a) and for AGN in general by Sobolewska & Papadakis (2009). Although they use 0.3-1.5 keV and 1.5-10 keV as their soft and hard band respectively, and define hardness ratio as H/S rather than the (H-S)/(H+S) used here, similar results are shown by Pal & Naik (2017).…”
Section: X-ray Spectral Variability and X-ray Energy Dependence Of Lagssupporting
confidence: 87%
“…Above 0.5 counts/s there is a very slight softening of the spectrum with increasing count rate. This spectral softening is similar to that found in NGC 4593 by Ursini et al (2016a) and for AGN in general by Sobolewska & Papadakis (2009). Although they use 0.3-1.5 keV and 1.5-10 keV as their soft and hard band respectively, and define hardness ratio as H/S rather than the (H-S)/(H+S) used here, similar results are shown by Pal & Naik (2017).…”
Section: X-ray Spectral Variability and X-ray Energy Dependence Of Lagssupporting
confidence: 87%
“…From these plots, it can be seen that a higher flux is associated with a lower hardness ratio, i.e. we observe a "softer when brighter" behaviour (see also Ursini et al 2016). During the first observation, both flux and spectral variability are particularly strong.…”
Section: Observations and Data Reductionmentioning
confidence: 61%
“…This is the first monitoring carried out by XMM-Newton and NuSTAR specifically designed to study the high-energy emission of an AGN through the analysis of its variability on time-scales of days. We reported preliminary results from a phenomenological timing analysis in Ursini et al (2016). Here we focus on the broad-band (0.3-80 keV) X-ray spectral analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the spin of supermassive BH is important but still challenging when using the relativistic X-ray reflection method (e.g., Reynolds 2014; Kammoun et al 2018). Although most of these concerned Seyfert galaxies have been extensively studied in X-ray (e.g., Nandra et al 1997Nandra et al , 2007Shu et al 2010;Walton et al 2013), up to now, only the BH spin of NGC 4151 has been found to be near-maximal (Keck et al 2015;Beuchert et al 2017), while ambiguous spins are still assumed in literature for the other sources (e.g., NGC 4593: Ursini et al 2016b;NGC 5548: Kammoun et al 2019a;NGC 4395: Kammoun et al 2019b). Therefore, we assume zero spin for the later three sources.…”
Section: Modeling Local Seyfert Galaxiesmentioning
confidence: 99%